Exploring resting EEG correlates of age-related hearing difficulties - Hunter, Cynthia R. (Frontiers in Neuroscience, 2026)
BackgroundHearing loss is among the largest modifiable risk factors for dementia and has been associated with age-related decline in working memory capacity. How hearing loss might impact brain function is not yet well understood. Neural indices that are associated with age-related cognitive impairment and dementia can be derived from resting-state electroencephalography (rEEG). However, it is not known whether these are associated with hearing loss. The goal of the current study was to explore the relation of hearing ability to rEEG indicators of pathological brain aging.DesignBivariate and partial correlations, controlling for age and education, of pure-tone-average (PTA) hearing loss, speech-in-noise ability, and self-reported hearing difficulty with oscillatory power in the alpha (8–13 Hz) and theta (4–7 Hz) bands as well as with individual alpha frequency (IAF) were explored in a sample of community-dwelling middle-aged and older adults (N = 62; 44 women; mean age = 67.18, range: 43–85). Correlations of the hearing factors with working memory capacity were also explored.ResultsCorrelations of rEEG measures with hearing ability measures were small-to-moderate (range: −0.05 to −0.25), with the only significant relation being that greater PTA hearing loss was associated with lower oscillatory power in the alpha band (bivariate rho(61) = −0.25, 95% CI: −0.47, −0.02; partial rho(59) = −0.23, 95% CI: −0.44, −0.01). Correlations of working memory with the hearing ability measures were also small-to-moderate in the bivariate analysis (range: −0.14 to −0.34) but weaker and not significant when age and education were controlled (range: −0.08 to −0.19).ConclusionPoorer hearing ability in middle-aged and older adults may be associated with reduced resting alpha power. The small-to-moderate effect size of this relation was comparable in this sample to the known association of hearing loss with working memory capacity. Further work is warranted to investigate alpha power as a possible marker of changes to brain function associated with hearing loss.